Komunikasi Perspektif Gender pada Anak Usia Dini Melalui Reproduksi Narasi Buku Cerita Anak Berarketip Gender - La Iba (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2014)
Internalization value since an early age will be rooted to life. Any discriminatory values and messages will not be found in the Islamic concept, both to women and men. The verses that reveal about the relationship between men and women show a message of equality between men and women. Thus, the values of equality should be developed at an early age children, both within the family and the pre-school educational institutions. In early childhood learning also needs to be developed the oriented learning of gender balance, to avoid learning of the gender bias values, both in the field of development and behavior formation and in the field of development of basic skills. The development of the formation of such behavior include the development of moral and religious values, as well as social and emotional development of the child; whereas the field of basic capabilities include cognitive abilities, language, motor, and art; needs to be developed by educators with equality and gender balance. Keywords: gender, early age children, reproduction